The Cambridge Companion to Nelson Mandela By Rita Barnard (ed) - Marthinus Conradie (Acta Academica, 2015)
From text: That Nelson Mandela has become an overdetermined signifier is axiomatic. Many scholars sensitive to the risks that inhere wherever this occurs have already pointed to the dangers posed by a diluted, provincial, and glossed-over framing of Mandela.